Molecular characterization, comparative genome analysis and resistance determinants of three clinical Elizabethkingia miricola strains isolated from Michigan - Chen, Shicheng; Agah, Grace; Blom, Jochen; Walker, Edward D. (Frontiers in Microbiology, 2025)
IntroductionElizabethkingia miricola is a gram-negative bacterium that causes life-threatening infections in vulnerable populations. Unlike other species in the Elizabethkingia genus, E. miricola also leads to meningitis-like diseases in aquatic invertebrates such as frogs, raising concerns about its zoonotic transmission potential. Management of its infection is complicated by unclear transmission pathways and multi-drug resistance.MethodsIn this study, we analyzed three clinical strains (E. miricola Mich-1, Mich-2, and Mich-3) isolated from patients in Michigan using morphology observations, biochemical tests, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF/MS), and genome sequencing.ResultsAverage Nucleotide Identity (ANI) analysis revealed that the Michigan strains were nearly identical and shared 96.52% identity with the type strain E. miricola DSM 14571, confirming their classification as E. miricola. Comprehensive comparative genomic analyses were conducted across 28 strains, including human isolates and strains from invertebrates like frogs. The strains exhibited open pan-genome characteristics. Mich-1 shared 3,199 genes (83.2%) with human isolates but fewer genes with frog-derived isolates (ranging from 3,319 to 3,375). This phylogenetic analysis highlights regional variation and the global diversity of E. miricola isolates, revealing connections between clinical and environmental strains. Antibiotic susceptibility testing revealed that the three clinical strains were resistant to 13 out of 16 tested drugs, with susceptibility only to trimethoprim/sulfamethoxazole and ciprofloxacin. The strains carried five β-lactamase-encoding genes (BlaB-10, BlaB-39, CME-1, CME-2, and GOB-25), conferring resistance to penams, cephalosporins, and carbapenems. Several virulence-associated genes were conserved across clinical and frog isolates. These genes contribute to stress adaptation, adherence, and immune modulation.DiscussionThis study underscores the evolutionary adaptability of E. miricola genomes, highlighting their capacity to acquire genetic traits that enable survival in diverse niches. This adaptability facilitates the emergence of more resistant and virulent strains, posing significant threats to both human and animal health.